Current Management of Dry Eye due to The Influence of drugs - Maria Vincentia Jessica; Larin Laudita; Kresten Desma Lina; Santi Anugrahsari (Jurnal MedScientiae, 2023)
Background, The most common complaints of irritation in the eyes that often bring patients to have their eyes checked are generally associated with dry eyes.  Dry eye disease (DED) is a disease associated with tear film instability due to multifactorial causes where the prevalence of DED with or without symptoms ranges from 5% to 50%.  Factors that cause dry eyes are the use of topical drugs and systemic drugs. Method. This literature review is in the form of a literature review with a descriptive approach. This literature review uses a scientific online databases that support the provision of data on topics raised according to titles, such as PubMed and Google Scholar with the keywords “Current” AND “Management” AND “Dry Eye” AND “Influence of Drugs” Conclusion, one of the factors for dry eye disease can occur due to the influence of drug.. The effect of dry eye is drug factors, namely systemic drugs and topical drugs. Treatment of dry eyes, which can be given artificial tears, increases the volume of the tear film and moisture on the surface of the eye.